2019
DOI: 10.1136/bmjpo-2018-000424
|View full text |Cite
|
Sign up to set email alerts
|

Cross-validated prediction model for severe adverse neonatal outcomes in a term, non-anomalous, singleton cohort

Abstract: ObjectiveThe aim of this study was to develop a predictive model using maternal, intrapartum and ultrasound variables for a composite of severe adverse neonatal outcomes (SANO) in term infants.DesignProspectively collected observational study. Mixed effects generalised linear models were used for modelling. Internal validation was performed using the K-fold cross-validation technique.SettingThis was a study of women that birthed at the Mater Mother’s Hospital in Brisbane, Australia between January 2010 and Apr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…An extra step forward could be screening to identify children that are at higher risk of experiencing neonatal asphyxia from a low risk population. Some studies have been conducted and have found that it is possible to predict infants that are at risk of severe adverse neonatal outcomes at term with moderate accuracy using an algorithm that combines maternal, intrapartum and ultrasound variables (28).…”
Section: Discussionmentioning
confidence: 99%
“…An extra step forward could be screening to identify children that are at higher risk of experiencing neonatal asphyxia from a low risk population. Some studies have been conducted and have found that it is possible to predict infants that are at risk of severe adverse neonatal outcomes at term with moderate accuracy using an algorithm that combines maternal, intrapartum and ultrasound variables (28).…”
Section: Discussionmentioning
confidence: 99%
“…The performance of development and validation datasets will be assessed via overall performance (R 2 ), calibration, discrimination, and clinical performance will be assessed through positive predictive value (PPV) and negative predictive value (NPV). A fixed false-positive cutoff of 10% will be used for PPV and NPV [38]. Calibration characterizes model performance in terms of agreement between predicted (expected) risk and observed risk and is reported using a calibration plot [39].…”
Section: Model Performancementioning
confidence: 99%
“…Backward stepwise elimination in a multivariable logistic regression model will be applied to remove non-signi cant factors with p-values greater than 0.100 in line with Akaike's Information Criterion (30). Finally, the risk prediction model will be applied and fully validated for each week gestation from 35 weeks (six total models: 35,36,37,38,40, and 41+ weeks).…”
Section: Model Developmentmentioning
confidence: 99%
“…The performance of development and validation datasets will be assessed via overall performance (R 2 ), calibration, discrimination and clinical performance will be assessed through positive predictive value (PPV), and negative predictive value (NPV). A xed false positive cut-off of 10% will be used for PPV and NPV (37).…”
Section: Model Performancementioning
confidence: 99%